Math, asked by vaishnavi4692, 9 months ago

2x plus 3y whole cube minus 2x minus 3y whole cube​

Answers

Answered by aditya121253
41

Answer:

Use the identity: a³ - b³ = (a - b)(a² + ab + b²)

(2x+3y)³ - (2x-3y)³

= [(2x + 3y) - (2x-3y) ][(2x-3y)² + (2x - 3y)(2x + 3y) + (2x + 3y)² ]

= [ 2x + 3y - 2x + 3y ][(4x² + 9y² - 12xy) + (4x² - 9y²) + (4x² + 9y² + 12xy) ]

= [6y][ 4x² + 9y² - 12xy + 4x² - 9y² + 4x² + 9y² + 12xy ]

= [6y][ 4x² + 4x² + 4x² + 9y² + 9y² - 9y² - 12xy + 12xy ]

= [6y][ 12x² + 9y²]

= 6y×3×(4x² + 3y²)

= 18y(4x² + 3y²)

Step-by-step explanation:

please give me like and follow me

Answered by nraj26
6

Answer:

Use the identity: a³ - b³ = (a - b)(a² + ab + b²)

Step-by-step explanation:

(2x+3y)³ - (2x-3y)³

= [(2x + 3y) - (2x-3y) ][(2x-3y)² + (2x - 3y)(2x + 3y) + (2x + 3y)² ]

= [ 2x + 3y - 2x + 3y ][(4x² + 9y² - 12xy) + (4x² - 9y²) + (4x² + 9y² + 12xy) ]

= [6y][ 4x² + 9y² - 12xy + 4x² - 9y² + 4x² + 9y² + 12xy ]

= [6y][ 4x² + 4x² + 4x² + 9y² + 9y² - 9y² - 12xy + 12xy ]

= [6y][ 12x² + 9y²]

= 6y×3×(4x² + 3y²)

= 18y(4x² + 3y²)

Similar questions